2009
DOI: 10.1148/radiol.2531081722
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Synovial Inflammation: Pixel-by-Pixel Dynamic Contrast-enhanced MR Imaging Time-Intensity Curve Shape Analysis—A Feasibility Study

Abstract: The pixel-by-pixel dynamic contrast-enhanced MR imaging TIC shape analysis may help distinguish patients with RA from control subjects on the basis of the relative number of type 4 TIC shapes. This study provides the rationale for future research to evaluate the utility of this approach in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 24 publications
0
30
0
1
Order By: Relevance
“…In a previous study, the early washout phase was explained by the back flux of contrast agent due to increased vascular permeability and/or the passive diffusion of contrast agent into effusion fluid. 18 In the knee and wrist, the washout phase is seen because contrast agent flows directly into the pannus from the vessels with high blood flow. On the other hand, as the partial synovial pannus in the finger joint is gradually supplied with blood via narrow peripheral arteries, the back flux of contrast agent due to increased vascular permeability may not necessarily have occurred.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study, the early washout phase was explained by the back flux of contrast agent due to increased vascular permeability and/or the passive diffusion of contrast agent into effusion fluid. 18 In the knee and wrist, the washout phase is seen because contrast agent flows directly into the pannus from the vessels with high blood flow. On the other hand, as the partial synovial pannus in the finger joint is gradually supplied with blood via narrow peripheral arteries, the back flux of contrast agent due to increased vascular permeability may not necessarily have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the relative number of Type 4 TIC shapes was significantly greater in patients with RA than in healthy control subjects; hence Type 4 TIC shapes were associated with RA. 18,19,23 Although these studies were performed in the knee, pannus formations were mainly classified as Type 4 in the RA hand as well due to the characteristics of inflamed synovial tissue related to increased tissue vascularization and permeability. However, as pointed out above, a part of pannus tissue located in the finger region was classified into other TIC types.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations